Modern control systems - Dorf, Richard C.; Bishop, Robert H. 1957- (Pearson, 2017)
The purpose of Dorf's Modern Control Systems, Thirteenth Edition is to present the structure of feedback control theory and to provide a sequence of exciting discoveries. The book demonstrates various real-world, global engineering problems while touching on evolving design strategies like green technology. Some of the themes at-hand include climate change, clean water, sustainability, waste management, emissions reduction, and minimizing energy. Throughout the text, students apply theory to the design and analysis of control systems.